2008
DOI: 10.1523/jneurosci.0008-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Myosin II Activation and Actin Reorganization Regulate the Mode of Quantal Exocytosis in Mouse Adrenal Chromaffin Cells

Abstract: Chromaffin cells of the adrenal medulla are innervated by the sympathetic nervous system. Stimulation causes chromaffin cells to fire action potentials, leading to the exocytosis of various classes of transmitters into the circulation. Low-frequency electrical stimulation (action potentials delivered at 0.5 Hz) causes adrenal chromaffin cells to selectively release catecholamines through a kiss-and-run fusion event. Elevated electrical stimulation (action potentials at 15 Hz) evokes fusion pore dilation, full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(118 citation statements)
references
References 50 publications
10
108
0
Order By: Relevance
“…Indeed, careful analysis of the dynamics of the secretory process led to the conclusion that the frequency of kiss-and-run exocytosis is 2-fold higher than that of full exocytosis in Ag-triggered RBL cells (48). Moreover, in the presence of cytochalasin D, which was previously shown to shift kiss-and-run to full exocytosis (49), the Ion/TPA-inhibitory Rabs turned inhibitory toward Ag.…”
Section: Discussionmentioning
confidence: 82%
“…Indeed, careful analysis of the dynamics of the secretory process led to the conclusion that the frequency of kiss-and-run exocytosis is 2-fold higher than that of full exocytosis in Ag-triggered RBL cells (48). Moreover, in the presence of cytochalasin D, which was previously shown to shift kiss-and-run to full exocytosis (49), the Ion/TPA-inhibitory Rabs turned inhibitory toward Ag.…”
Section: Discussionmentioning
confidence: 82%
“…Rather, based on amperometric analysis, the fused granule remains stable as an Ω-figure for at least the duration of catecholamine release. This behavior may simply be a result of the dense proteinacious core within the granule lumen that blocks granule collapse, or it may also include other extrinsic factors such as stabilization by the cytoskeleton [33,34]. Further experimentation will be required to reveal the factors responsible for Ω-figure stabilization under light electrical stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is not reflected in the more sensitive variance analysis provided in figure 3, indicating that dilation must occur to some degree, but does not proceed to completion. Indeed, recent work has suggested that mechanisms other than dynamin function contribute to fusion pore dilation [33,34].…”
Section: A Role For Dynamin I In High Frequency-evoked Exocytosismentioning
confidence: 99%
“…Inhibition of phosphorylation by the myosin light chain kinase (MLCK) at sites Tyr18 and Ser19 of Myosin2, slowed down the opening of the fusion pore, during the release of catecholamines and peptide transmitters in chromaffin cells (Doreian, et al, 2008;Doreian, et al, 2009;Neco, et al, 2008). Similarly, phosphorylation at Ser 19 of Myosin2 by MLCK was shown to be necessary for maintaining the opening of the fusion pore in pancreatic cells (Bhat & Thorn, 2009).…”
Section: Phospho-regulation Beyond Fusionmentioning
confidence: 99%